The Influence of post-biblical Hebrew and Aramaic on the translator of Septuagint Isaiah - Byun, Seulgi L. (Library of Hebrew bible/Old Testament studies, 2017)
"An examination of the Septuagint text of Isaiah with special focus on whether or not Post-biblical Hebrew and Aramaic have had an impact upon the translation of the text"--